High Speed Problems of Aircraft and Experimental Methods - Donovan, A. F. (Allen F.) (Book collections on Project MUSE., 1961)
Volume VIII of the High Speed Aerodynamics and Jet Propulsion series. This volume includes: performance calculation at high speed; stability and control of high speed aircraft; aeroelasticity and flutter; model testing; transonic wind tunnels; supersonic tunnels; hypersonic experimental facilities; low density wind tunnels; shock tube; wind tunnel measurements; instrumented models in free flight; piloted aircraft testing; free flight range methods. Originally published in 1961. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.